2015
DOI: 10.1002/ird.1915
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Drip‐ and Furrow‐Irrigated red Pepper Yield, Yield Components, Quality and net Profit Generation

Abstract: The effects of different irrigation regimes on yield and quality and net profit of processing red pepper irrigated with drip and furrow irrigation systems under field conditions in the Mediterranean region of Turkey were evaluated over two years. The treatments for drip consist of full irrigation (DFI), deficit irrigation DDI‐75, D‐PRD‐50, DF‐PRD‐50 and DDI‐50, and for furrow: full irrigation (FFI), fixed alternative furrow (FAF‐50) and PRD furrow (FPRD‐50). FAF‐50 and FPRD‐50 received 50% of water applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
6
11
0
Order By: Relevance
“…Moreover, SMC in treatment ØB fell 5 times below treshhold (80% of FC), and due to soil water stress during mass fructification resulted in lower yield compared with drip fertigation treatments. Also, the results from present investigation correspond with those of Sezen et al (2015), where drip irrigated pepper was compared with furrow and Tanaskovik et al (2016), where drip fertigated tomato was compared with banded and furrow irrigated. For high pepper yields, an adequate water supply (Kirnak et al, 2016) and relatively moist soils are required during the total growing 528 period (Shao et al, 2010;Sezen et al, 2014).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, SMC in treatment ØB fell 5 times below treshhold (80% of FC), and due to soil water stress during mass fructification resulted in lower yield compared with drip fertigation treatments. Also, the results from present investigation correspond with those of Sezen et al (2015), where drip irrigated pepper was compared with furrow and Tanaskovik et al (2016), where drip fertigated tomato was compared with banded and furrow irrigated. For high pepper yields, an adequate water supply (Kirnak et al, 2016) and relatively moist soils are required during the total growing 528 period (Shao et al, 2010;Sezen et al, 2014).…”
Section: Resultssupporting
confidence: 83%
“…Furthermore, pepper is among the most sensitive horticultural plants to water deficit stress (Delfine et al, 2002;Ferrara et al, 2011). Such sensitivity was reported in some studies on the fresh and dry matter yield reductions as affected by different irrigation techniques and regime (Antony and Singandhupe, 2004;Sezen et al, 2006;González-Dugo et al, 2007;Candido et al, 2009;Kurunc et al, 2011;Aladenola and Madramootoo, 2014;Sezen et al, 2014;Sezen et al, 2015;Kuşçu et al, 2016). Also, nitrogen is another limiting factor along with water deficit in arid and semi-arid regions (Cetin and Akinci, 2015).…”
Section: Introductionmentioning
confidence: 91%
“…Kong et al (2012), through drip irrigation determined WP values between 7.76 kg m -3 and 10.71 kg m -3 in bell pepper. Sezen et al (2015), reports of WP of 6.9 kg m -3 and IWP of 5.7 kg m -3 by applying irrigation water of 570.4 mm for the whole growing season at intervals of 3 to 6 days. Guang-Cheng et al (2010), determined the WP and IWP hot pepper in greenhouses values oscillate between 6.7 to 10.4 kg m -3 and 6.3 to 10.6 kg m-3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, highest quality fruit (increased weight and reduced dry matter and sunscald incidence) was obtained under shade. Sezen et al (2015), reported increased fruit yield to augmented fruit number In addition, a uniform supply of water in the soil throughout the growing season is needed to prevent poor fruit size and shape and to improve yield. Rylski and Spigelman (1986), reported changes in plant development due to the shading affected.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of regular and appropriate supply of water during fruit development stages was highlighted earlier by Subramanian et al (1997), Panigrahi et al (2012) and Ghosh & Pal (2016). Further, Sezen et al (2015) also reported a gradual increases in yield with increased level of irrigation, while, Kumar et al (2013) reported a significant reduction in the number of fruits and fruit yield with highest irrigation level. At highest irrigation level (1.0V), the number of fruits and fruit weight was reduced.…”
Section: Yield Parametersmentioning
confidence: 96%